2012
DOI: 10.2147/idr.s25890
|View full text |Cite
|
Sign up to set email alerts
|

Clinical update on linezolid in the treatment of Gram-positive bacterial infections

Abstract: Gram-positive pathogens are a significant cause of morbidity and mortality in both community and health care settings. Glycopeptides have traditionally been the antibiotics of choice for multiresistant Gram-positive pathogens but there are problems with their use, including the emergence of glycopeptide-resistant strains, tissue penetration, and achieving and monitoring adequate serum levels. Newer antibiotics such as linezolid, a synthetic oxazolidinone, are available for the treatment of resistant Gram-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 169 publications
(193 reference statements)
1
17
0
Order By: Relevance
“…On the contrary, in the control sample, linezolid displayed higher activity in the first hour; however, it loses effectiveness over time, as depicted in Figure 7 A,C. The control inhibition zone in the first hour was close to ~30 mm, but over time was decreasing, reaching ~8 mm at 48 h. In contrast, PGAH-Li started with an inhibition zone of ~11 mm and progressively rose to complete an inhibition zone of 23 mm at 48 h. These results are in concordance with the quantitative analysis of antibacterial activity against the E. faecium that is exhibited in Figure 7 D. The data revealed that, in the control, the bacterial colony forming unit (CFU) increases over time, demonstrating that the antibiotic loses its activity until 72 h. Conversely, the assay with the PGAH-Li release medium significantly inhibits bacterial proliferation, suggesting that the linezolid acted as a bacteriostatic agent against Enterococcus faecium [ 37 ]. An additional experiment with PGAH without linezolid was performed.…”
Section: Resultssupporting
confidence: 83%
“…On the contrary, in the control sample, linezolid displayed higher activity in the first hour; however, it loses effectiveness over time, as depicted in Figure 7 A,C. The control inhibition zone in the first hour was close to ~30 mm, but over time was decreasing, reaching ~8 mm at 48 h. In contrast, PGAH-Li started with an inhibition zone of ~11 mm and progressively rose to complete an inhibition zone of 23 mm at 48 h. These results are in concordance with the quantitative analysis of antibacterial activity against the E. faecium that is exhibited in Figure 7 D. The data revealed that, in the control, the bacterial colony forming unit (CFU) increases over time, demonstrating that the antibiotic loses its activity until 72 h. Conversely, the assay with the PGAH-Li release medium significantly inhibits bacterial proliferation, suggesting that the linezolid acted as a bacteriostatic agent against Enterococcus faecium [ 37 ]. An additional experiment with PGAH without linezolid was performed.…”
Section: Resultssupporting
confidence: 83%
“… 38 Resistance of enterococci to linezolid is rare and usually mediated by mutations 23S rRNA target. 39 It has been associated with previous linezolid therapy, although nosocomial acquisition of resistant enterococci has been also reported. 39 41 Resistance mechanisms were first described for E. faecium and S. aureus , and later also for E. faecalis , but they remain rare, affecting less than 1% of all strains, as documented in a surveillance study of 7608 clinical isolates of enterococci from years 2004–2012 collected in the USA.…”
Section: Bloodstream Infectionsmentioning
confidence: 99%
“…Linezolid is commonly used to treat resistant gram positive infections (36). Induction of antimicrobial resistance, along with the drug’s high cost, make the use of linezolid in this manner impractical (37). Our results show however that IFNγ could serve as a significant drug target for specific populations at high risk for secondary infections due to influenza.…”
Section: Discussionmentioning
confidence: 99%